2017
DOI: 10.1074/jbc.m117.777243
|View full text |Cite
|
Sign up to set email alerts
|

Nanomolar nitric oxide concentrations quickly and reversibly modulate astrocytic energy metabolism

Abstract: Nitric oxide (NO) is an intercellular messenger involved in multiple bodily functions. Prolonged NO exposure irreversibly inhibits respiration by covalent modification of mitochondrial cytochrome oxidase, a phenomenon of pathological relevance. However, the speed and potency of NO's metabolic effects at physiological concentrations are incompletely characterized. To this end, we set out to investigate the metabolic effects of NO in cultured astrocytes from mice by taking advantage of the high spatiotemporal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 66 publications
0
28
0
Order By: Relevance
“…Recently, NO has been reported to function as an important cell signal, which functions over the entire lifespan. Studies in animals focus on NO due to not only its role as a potential target in cancer therapy, but also its functions in cell death, oxygen sensing and energy metabolism (Nunes et al, 2011;Kubo et al, 2016;San Martín et al, 2017). In plants, NO was shown to regulate seed germination, root and pollen tube growth, flowering, adaptive responses to abiotic stresses and pathogenesis (Bellin et al, 2013;Santolini et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, NO has been reported to function as an important cell signal, which functions over the entire lifespan. Studies in animals focus on NO due to not only its role as a potential target in cancer therapy, but also its functions in cell death, oxygen sensing and energy metabolism (Nunes et al, 2011;Kubo et al, 2016;San Martín et al, 2017). In plants, NO was shown to regulate seed germination, root and pollen tube growth, flowering, adaptive responses to abiotic stresses and pathogenesis (Bellin et al, 2013;Santolini et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Binding of the test molecule, triggers a conformational change that affects the relative distance and/or orientation between the acceptor/donor fluorescent proteins, causing an increase or decrease in FRET efficiency (Miyawaki et al 1997). These genetically-encoded indicators have been instrumental to decipher molecular mechanism involved in fast modulation of oxidative and glycolytic metabolism in the brain (Baeza-Lehnert et al 2018;Fernandez-Moncada et al 2018;Lerchundi et al 2015;Machler et al 2016;San Martin et al 2017;San Martin et al 2014b;Valdebenito et al 2016). Being fluorescent and geneticallyencoded, these tools have a great potential to develop cell-based high-throughput methods for the pharmaceutical industry (Mendelsohn et al 2018;Schaaf et al 2018;Schaaf et al 2017;Zhao et al 2015;Zhao et al 2018).…”
mentioning
confidence: 99%
“…Being fluorescent and geneticallyencoded, these tools have a great potential to develop cell-based high-throughput methods for the pharmaceutical industry (Mendelsohn et al 2018;Schaaf et al 2018;Schaaf et al 2017;Zhao et al 2015;Zhao et al 2018). Using a FRET-based lactate indicator Laconic (San Martin et al 2013), we have observed that the mitochondrial damage induced by sodium azide or physiological mitochondrial modulator signals such as nitric oxide, produces a fast and acute cytosolic lactate accumulation (San Martin et al 2017;San Martin et al 2013). A phenomenon explained primarily by a reduction of mitochondrial pyruvate consumption and secondary glycolysis activation (Bittner et al 2010;San Martin et al 2017;San Martin et al 2014a).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, an alternative to the lactate shuttle hypothesis could be that both neurons and astrocytes produce lactate during brain activation and that this lactate pool can then be metabolized at a later point by both cell types (and maybe other cells) or dispersed within the brain parenchyma. However the story of neuronal coupling ends, these new data from San Martín et al (7) provide an interesting chapter that advances our understanding of astrocyte metabolism. …”
mentioning
confidence: 99%